Analisis Rasio Aktivitas Untuk Menilai Kinerja Keuangan Pada PT Adaro Minerals Indonesia Tbk yang Terdaftar Di Bursa Efek Indonesia (BEI) - Zuraidaning Tyas, Karunia; Dewanty, Amalia Rahmayang; Sechan, Cathalina; Mukharomah, Indri Nur (Perwira Journal of Economics & Business, 2023)
Analysis of financial statements is necessary for the company to assess the performance of the company and to compare the condition of the company from the previous year. One of the ratios used in conducting the analysis is the activity ratio. The activity ratio is useful for analyzing the use of resources owned and to support the company's activities. There are several types of activity ratios that are used as a measuring tool to determine the company's ability to use its assets, namely the turnover of total assets, the turnover of working capital, the turnover of fixed assets, the turnover of inventory, and the turnover of receivables. Based on the results of the calculation of the activity ratio in PT. Adaro Minerals Indonesia Tbk shows that there was an increase in all types of ratios in 2020 to 2021, but the results achieved are still below industry standards which shows that the company's performance is still not good compared to other similar industries. This needs to be a vigilance of the company to always improve performance and have high competitiveness